PENGARUH SEMANGAT KERJA DAN STRESS KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT PLN (PERSERO) UNIT PELAKSANA PELAYANAN PELANGGAN (UP3) PINRANG - Kamiluddin, A.Rifki; Syukri, Fitriyani (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
Spirit at work is a person's desire and sincerity to do his job well and be disciplined to achieve maximum work performance. Stress is an adaptive response to a person's condition that is felt to be threatening or challenging. Productivity is nothing but talking about human or individual behavior, namely their productivity behavior. This study aims to determine whether there is an effect of work spirit (X1) and work stress (X2) on the work productivity of employee. The data collection techniques used in this study were questionnaires, observations, and literature studies. The sample in this study amounted to 42 respondents. The data analysis technique in this study used multiple linear regression analysis with the help of a computerized system (computer program IBM Statistics SPSS 23). The results of research conducted on the first hypothesis, that work spirit of employee has no significant effect on work productivity of employees at PT PLN (PERSERO) Unit Pelaksana Pelayanan Pelanggan (UP3) Pinrang. In the second hypothesis, it can be concluded that work stress of employee has no significant effect on work productivity of employees at PT PLN (PERSERO) Unit Pelaksana Pelayanan Pelanggan (UP3) Pinrang.